Pelatihan dan Edukasi Berbagai Jenis Dan Ukuran Kemasan Produk Olahan Meningkatkan Nilai Jual Produk - Yessy Rosalina; Firmansyah Firmansyah; Syafnil (JPM: Jurnal Pengabdian Masyarakat, 2025)
Rejang Lebong is a regency in Bengkulu Province, located near South Sumatra Province, making it a popular tourist destination for both local and non-local visitors. To support tourism development and enhance the economic value of the community, the Social Forestry program has established Kelompok Perempuan Pemerhati Lingkungan (KPPL), which include KPPL Maju Bersama, KPPL Karya Mandiri, KPPL Sumber Jaya, and KPPL Sejahtera. The purpose of this community service program is to provide training for Kelompok Perempuan Pemerhati Lingkungan (KPPL) on selecting appropriate and economical packaging variations in terms of type and size, ensuring they are marketable to consumers while maximizing profits. Additionally, the program aims to educate KPPL members on selecting and innovating packaging types suitable for post-harvest processed products. The target audience of this community service initiative consists of KPPL members in Rejang Lebong Regency, Bengkulu Province. This target group is expected to have the potential to enhance and share knowledge about proper and diverse food packaging, contributing to both food protection and consumer appeal. The methods employed in this program include coordination and socialization, counseling, and demonstrations. Training and education on the types and significance of packaging serve as strategic steps to increase the added value of local products, particularly for MSME (Micro, Small, and Medium Enterprises) actors. By understanding the right packaging types, attractive designs, and their environmental impact, the target audience can maintain product quality in the market. Despite the challenges faced, this training and education initiative is expected to encourage the target audience to be more creative in utilizing packaging as an effective marketing tool.